Modeling of composite plates based on Reissner's Mixed Variational Theorem with variables separation. (1st February 2016) - Vidal, P.; Gallimard, L.; Polit, O.
Abstract: In this work, the modeling of laminated composite plates is performed through a variables separation approach based on a Reissner's Variational Mixed Theorem (RMVT). Both the displacement and transverse stress fields are approximated as a sum of separated functions of the in-plane coordinates x, y and the transverse coordinate z . This choice yields to a non-linear problem that can be solved by an iterative process. That consists of solving a 2D and 1D problem successively at each iteration. In the thickness direction, a fourth-order expansion in each layer is considered. For the in-plane description, classical Finite Element method is used. Numerical examples involving several representative laminates are addressed to show the accuracy of the present LayerWise (LW) method. It is shown that it can provide quasi-3D results less costly than classical LW computations. In particular, the estimation of the transverse stresses which are of major importance for damage analysis is very good.